Critical timing of gastrostomy insertion in a child with cystic fibrosis. (October 2015) - Grime, Christopher J.; Greenaway, Catherine; Clarke, Simon; Balfour-Lynn, Ian M.
Summary: Pulmonary exacerbations and malabsorption in children with cystic fibrosis (CF) can lead to faltering growth and poor weight gain. Children with a higher BMI (body mass index) show a slower decline in lung function. Our specialist CF centre has experienced a death following gastrostomy insertion in a young CF child, despite maximal medical intervention, which has made us reflect on our practice and the urgency with which we discuss the option for a gastrostomy to improve nutrition.